(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Government sponsorship programmes have become an important policy intervention to improve access to secondary education for learners from economically disadvantaged households in Kenya. Despite the expansion of bursary schemes, concerns remain regarding their effectiveness in improving students' academic performance. This study examined the influence of government sponsorship on the academic performance of students in public secondary schools in Lugari Sub-County, Kakamega County, Kenya. The study employed a mixed-methods research design, combining quantitative and qualitative approaches to provide a comprehensive understanding of the relationship between sponsorship and academic achievement. A sample of 376 respondents comprising sponsored students, class teachers, and parents was selected using purposive sampling. Data were collected using structured questionnaires and interview schedules. Quantitative data were analysed using descriptive statistics, Pearson correlation analysis, and multiple regression analysis with the aid of the Statistical Package for the Social Sciences (SPSS), while qualitative data were analysed thematically. The findings revealed that government sponsorship had a statistically significant positive influence on students' academic performance. Pearson correlation analysis demonstrated a strong positive relationship between government sponsorship and academic performance (r = 0.818, p < .001). Qualitative findings further showed that bursary support reduced financial constraints, improved school attendance, enhanced access to learning materials, and enabled learners to concentrate on their studies. The study concludes that government sponsorship contributes significantly to improved educational outcomes by reducing financial barriers that hinder academic success. The study recommends increasing bursary allocations, ensuring timely disbursement of funds, and strengthening monitoring mechanisms to maximize the effectiveness of government sponsorship programmes.